Convergence of one-dimensional random processes - Vila Gabriel, Roberto (2023)
In this paper we extensively develop some of the results obtained in reference (Cioletti et al., 2017). We use the Wasserstein distance to obtain some central limit type theorems for one-dimensional random processes having positive associated dependence.